Ubiquitination of Neuronal Nitric-oxide Synthase in the Calmodulin-binding Site Triggers Proteasomal Degradation of the Protein - Clapp, Kelly M. (American Society for Biochemistry and Molecular Biology, 2012)
Nitric-oxide synthase, a cytochrome P450-like hemoprotein enzyme, catalyzes the synthesis of nitric oxide, a critical signaling molecule in a variety of physiological processes. Our laboratory has discovered that certain drugs suicide-inactivate neuronal nitric-oxide synthase (nNOS) and lead to the preferential ubiquitination of the inactivated nNOS by an Hsp70- and CHIP (C terminus of Hsc70-interacting protein)-dependent process. To further understand the process by which altered nNOS is recognized, ubiquitinated, and proteasomally degraded, we examined the sites of ubiquitination on nNOS. We utilized an in vitro ubiquitination system containing purified E1, E2 (UbcH5a), Hsp70, and CHIP that recapitulates the ability of the cells to selectively recognize and ubiquitinate the altered forms of nNOS. LC-MS/MS analysis of the tryptic peptides obtained from the in vitro ubiquitinated nNOS identified 12 ubiquitination sites. Nine of the sites were within the oxygenase domain and two were in the calmodulin-binding site, which links the oxygenase and reductase domains, and one site was in the reductase domain. Mutational analysis of the lysines in the calmodulin-binding site revealed that Lys-739 is a major site for poly-ubiquitination of nNOS in vitro and regulates, in large part, the CHIP-dependent degradation of nNOS in HEK293 cells, as well as in in vitro studies with fraction II. Elucidating the exact site of ubiquitination is an important step in understanding how chaperones recognize and trigger degradation of nNOS.